Elastic properties of arteries in hypertensive patients with hypertensive nephropathy and chronic stable angina - I.M. Fushtei; I.A. Kulinich; D.P. Myrnyi (Patologìâ)
Arterial wall changes are one of the arterial hypertension (AH) earliest complications. Hypertensive nephropathy is the widespread complication of AH which makes a substantial contribution to end stage renal disease. The aim of our work is the determination of specific features of peripheral arteries blood flow in patients with arterial hypertension in combination with stable angina depending on hypertensive nephropathy. 120 patients were examined with computerized tetrapolar electric impedance plethysmography. Significant changes of arterial circulation were revealed in all groups. Large vessels tonus in patients with AH and stable angina increased significantly. There were no changes of large vessels tonus in patients with hypertensive nephropathy. Tonus of femoral artery, medium and small arteries of hip had no significant relation with stable angina and hypertensive nephropathy. Tonus of internal carotid artery was significantly less in patients with AH and stable angina and hadn’t relation with nephropathy. Tonus of medium and small arteries of shoulder hadn’t relation with stable angina and was significantly higher in patients with hypertensive nephropathy than in those without nephropathy.